(7t-2)+4(3t+1)=-3(6-3t)

Simple and best practice solution for (7t-2)+4(3t+1)=-3(6-3t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7t-2)+4(3t+1)=-3(6-3t) equation:



(7t-2)+4(3t+1)=-3(6-3t)
We move all terms to the left:
(7t-2)+4(3t+1)-(-3(6-3t))=0
We add all the numbers together, and all the variables
(7t-2)+4(3t+1)-(-3(-3t+6))=0
We multiply parentheses
(7t-2)+12t-(-3(-3t+6))+4=0
We get rid of parentheses
7t+12t-(-3(-3t+6))-2+4=0
We calculate terms in parentheses: -(-3(-3t+6)), so:
-3(-3t+6)
We multiply parentheses
9t-18
Back to the equation:
-(9t-18)
We add all the numbers together, and all the variables
19t-(9t-18)+2=0
We get rid of parentheses
19t-9t+18+2=0
We add all the numbers together, and all the variables
10t+20=0
We move all terms containing t to the left, all other terms to the right
10t=-20
t=-20/10
t=-2

See similar equations:

| 18v+4-7v=-5+10v | | 90-x=2(180-(90-x))-6 | | 0.1-x/0.1+x=0.1 | | 6-7x=7x-10x=2 | | 0=0.1x-x | | 4x+23=14(5x-8) | | 19-2x=21 | | 2+17x+70=180 | | 100+50x=150+40x | | -5(6x+8)=-30x-40 | | 4x+21=12(5x-8) | | -7n+4=-5n-2 | | 6n-(n+7)=5n-7 | | 4x+23=12(5x-8) | | -10-f=10+f | | -27=y-18 | | (4x/5)-x=(x/15-(20/3) | | -15|3x-2|=-15 | | 5(5x+1)=5 | | 2(p−48)=96 | | 0.7x-7=3.5x-21 | | 5y+3y+6=54 | | 3a-4=a+5 | | 13r-17=12r | | 8w=8+10w | | g/2+41=51 | | 4.6g+6=1.6g+24 | | -3(x-15)=-54 | | 15x+12+12x+30=48 | | -9u=-10u+5 | | -5(7-6x)=25 | | 9(u+3)=90 |

Equations solver categories